2018
DOI: 10.1159/000496205
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia but Not Hyperglycemia Is Associated with Mortality in Critically Ill Patients with Diabetes

Abstract: Background: Both severe hyperglycemia (> 200 mg/dL) and hypoglycemia (≤70 mg/dL) are known to be associated with increased mortality in critically ill patients. Therefore, we investigated associations of a single episode of blood glucose deviation (concentration either ≤70 mg/dL and/or > 200 mg/dL) during an intensive care unit (ICU) stay with mortality in these patients. Methods: A total of 4,986 patients (age 65 ± 15 years; 39% female; 14% type 2 diabetes [T2DM] based on medical records) admitted to a German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…In addition to the change in glycaemic control methods before and after admission to the ICU, patients with a history of diabetes are more prone to glycaemic-related complications [ 30 ]. Some researchers have pointed out that the severity of hypoglycaemia in patients with a history of diabetes is greater than that in patients without a history of diabetes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the change in glycaemic control methods before and after admission to the ICU, patients with a history of diabetes are more prone to glycaemic-related complications [ 30 ]. Some researchers have pointed out that the severity of hypoglycaemia in patients with a history of diabetes is greater than that in patients without a history of diabetes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pre-existing diabetes, dissimilar correlations between blood glucose levels and outcomes were reported. In critically ill diabetic patients, hypoglycemia was found to be associated with a higher mortality rate (28,29). Regarding sepsis, some studies demonstrated a risk of admission hyperglycemia, whereas other studies reported only a risk of early hypoglycemia (15,23,30).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of a single episode of blood glucose deviation (concentration <70 and/or >200 mg/dL) during ICU stay in patients with sepsis, AMI and congestive heart failure found that for patients suffering from type 2 diabetes mellitus (T2DM), hypoglycaemia (odds ratio = 2.94) but not hyperglycaemia was associated with increased mortality. In patients without T2DM, both hyper‐ and hypoglycaemia were associated with adverse outcomes 51 . For type 2 diabetes patients, the diabetes‐related complication was the major determinant of hospital mortality rather than diabetes per se, HbA1c level or initial blood glucose level.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…In patients without T2DM, both hyper-and hypoglycaemia were associated with adverse outcomes. 51 For type 2 diabetes patients, the diabetes-related complication was the major determinant of hospital mortality rather than diabetes per se, HbA1c level or initial blood glucose level. Initial blood glucose levels did not differ significantly between surviving and deceased diabetic sepsis patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%